(untitled) (Nativa, 2022)
ABSTRACT: Micropropagation is one technology to propagate endemic species of the Ferruginous Rupestrian Grasslands when in vitro genetic conservation is sought. The present study aimed to assess the breaking of dormancy, in vitro establishment, multiplication, elongation, rooting, and acclimatization of Mimosa calodendron from culture in a temporary immersion bioreactor system. The seeds used for the experiments were from plants originating from the Ferruginous Rupestrian Grasslands. The percentage of contamination, oxidation, unresponsive seeds, germination, number of buds per explant, shoot length, senescence, percentage of adventitious rooting, and acclimatization were assessed. The breaking of dormancy was most successful by mechanical scarification (80% germination). Immersion in sodium hypochlorite for 5 minutes was the most efficient treatment for in vitro establishment (90%). For the in vitro multiplication and elongation phase, the use of liquid culture medium from cultivation in a temporary immersion bioreactor was the most suitable for the characteristics number of buds per explant (2.55 buds), vigor (1.1), oxidation (1.3) and senescence (1.3) according to the score’s scale. Regardless of the in vitro cultivation method, the percentages of rooting and acclimatization were satisfactory, and it was possible to obtain complete plants in 190 days. Palavras-chave: in vitro propagation; Ferruginous Rupestrian Grasslands; endemic species. Produção de mudas de Mimosa calodendron Mart. ex Benth. em biorreator de imersão temporária RESUMO: A micropropagação é uma alternativa para a propagação de espécies endêmicas do Campo Rupestre Ferruginoso, quando se busca a conservação genética in vitro. O trabalho teve como objetivo avaliar a superação de dormência, estabelecimento in vitro, multiplicação, alongamento, enraizamento e aclimatização de Mimosa calodendron a partir do cultivo em sistema de biorreator de imersão temporária (BIT). As sementes utilizadas para os experimentos foram provenientes de plantas oriundas do Campo Rupestre Ferruginoso. A porcentagem de contaminação, oxidação, sementes não responsivas, germinação, número de gemas por explante, comprimento de brotos, senescência, porcentagem de enraizamento e aclimatização foram avaliados. A superação de dormência por escarificação mecânica (80% de germinação) foi a mais adequada para a superação de dormência. A imersão em hipoclorito de sódio por 5 minutos foi o tratamento mais eficiente para o estabelecimento in vitro (90%). Para a fase de multiplicação e alongamento in vitro, o uso do meio de cultivo líquido a partir do cultivo em biorreator de imersão temporária foi o mais adequado para as características número de gemas por explante (2,55 gemas), vigor (1,1), oxidação (1,3) e senescência (1,3) de acordo à escala de notas. Independentemente do método de cultivo in vitro, a porcentagem de enraizamento e aclimatização foram satisfatórios, sendo possível obter plantas completas em 190 dias. Keywords: propagação in vitro; Campo Rupestre Ferruginoso; espécie endêmica.